Eocene Paleoclimatic Implications in the Bayat Basin Based on Nannofossil Distribution - Rifa'i, Muhammad; Choiriah, Siti Umiyatun; Akmaluddin (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
The Middle–Late Eocene represents a critical interval of greenhouse climate evolution following the Early Eocene Climatic Optimum (EECO), yet quantitative paleoclimate records from low-latitude Southeast Asia remain scarce. This study presents a multi-proxy calcareous nannofossil-based reconstruction of surface-water conditions from the Gamping–Wungkal Formation in the Bayat Basin, southern Java. Detailed stratigraphic logging and systematic sampling along a 60 m section were combined with quantitative assemblage analysis and Scanning Electron Microscope validation. Biostratigraphic evaluation assigns the studied interval to the NP17 zone (Middle–Late Eocene). Paleoclimatic reconstruction integrates the Reticulofenestra Size Ratio (RSR), Warm-Water Index (WWI), Discoaster Abundance Ratio (DAR), and total Reticulofenestra abundance. Assemblages are dominated by medium- to large-sized Reticulofenestra and persistent Discoaster occurrences, indicating warm, oligotrophic, and stratified surface-water conditions. Despite global post-EECO cooling trends documented in mid- and high-latitude records, the Bayat data suggest sustained tropical greenhouse conditions during NP17. These findings are consistent with emerging evidence of latitudinal variability in Eocene climate evolution and establish the Bayat Basin as an important low-latitude archive for evaluating Paleogene greenhouse dynamics in Southeast Asia.